1993
DOI: 10.1525/ap3a.1993.4.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Weapon Technology, Prey Size Selection, and Hunting Methods in Modern Hunter‐Gatherers: Implications for Hunting in the Palaeolithic and Mesolithic

Abstract: The ethnographic and ethnohistoric literature on a global sample of 96 recent hunting peoples was surveyed to explore the relationships between weapons, prey body-size, and terrestrial hunting techniques. Findings include: (1) an association between the use of hand-delivered spears, large-bodied prey, and hunting techniques dependent on physiographic features and specific terrain types; (2) less dependence on terrain features in hunting with atlatl-propelled darts, and; (3) use of the bow and arrow without reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0
26

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 39 publications
2
141
0
26
Order By: Relevance
“…The use of spears ( Figure 1) is strongly associated with the hunting of large animals [27,130]; and indeed, the use of spears in elephant hunting appears in several ethnographic documentations.…”
Section: Hunting With Spearsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of spears ( Figure 1) is strongly associated with the hunting of large animals [27,130]; and indeed, the use of spears in elephant hunting appears in several ethnographic documentations.…”
Section: Hunting With Spearsmentioning
confidence: 99%
“…In a study surveying 96 contemporary hunting groups, Churchill [130] identified an association between the use of hand-delivered spears, whether thrust or thrown, and the hunting of large prey, including elephants. He claims that "this may be because spears are the best tool for dispatching large animals or because the hunting techniques required to take game with hand spears generally work better with larger prey" [130] (p. 19).…”
Section: Hunting With Spearsmentioning
confidence: 99%
“…Hughes (1997:349-350) identified accuracy, range, and penetration as important performance criteria; Wilhelmsen (2001:112-115) added aerodynamic properties related to flight stability. Variation in performance requirements can be measured, among other ways, by characteristics like tip acuity, bilateral plan symmetry, and cross-section form and perimeter (Hughes 1997;Wilhelmsen 2001; see also Beck 1998:25;Chesier and Kelly 2006;Churchill 1993;Collins 2007:72;Ratto 2003: Table 5.2a,b;Shott 1993). From hafted ethnographic and archeological specimens of known status, Hughes distinguished points of thrusting spears, darts, and arrows, which occupied somewhat overlapping segments of continua in mass, cross-section area and perimeter (1998 :Tables III-IV; see also Ratto 2003:215-216).…”
Section: If Points Evolve How Do We Measure the Process?mentioning
confidence: 99%
“…According to Binford (1984) and Churchill (1993), all recent hunters, including the Hadza and the Bushmen, use projectile technologies such as the bow and arrow. ESA hunters might have used hand-cast spears, but spears are rarely used in ambush, approach, or encounter hunting.…”
Section: Tracking Abilitiesmentioning
confidence: 99%
“…Spears are ineffective at long distances, and their use poses substantial dangers to a hunter. According to Churchill (1993), the distance from which throwing spears are cast at prey by recent hunters averages only 7.8 AE 2.2 m (n ¼ 14). Moreover, these distances mostly represent kills of animals that had already been immobilized and include data only for tipped spears.…”
Section: Tracking Abilitiesmentioning
confidence: 99%